2016 23rd International Conference on Pattern Recognition (ICPR) 2016
DOI: 10.1109/icpr.2016.7900232
|View full text |Cite
|
Sign up to set email alerts
|

A constrained clustering based approach for matching a collection of feature sets

Abstract: In this paper, we consider the problem of finding the feature correspondences among a collection of feature sets, by using their point-wise unary features. This is a fundamental problem in computer vision and pattern recognition, which also closely relates to other areas such as operational research. Different from two-set matching which can be transformed to a quadratic assignment programming task that is known NP-hard, inclusion of merely unary attributes leads to a linear assignment problem for matching two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…In [34], the clustering perspective is used in an algorithm that iterates between a matching step and the selection of mean features (similarly to k-means); this algorithm is sensitive to the initialization used, and multiple iterations are typically needed in order to achieve convergence.…”
Section: Clusteringmentioning
confidence: 99%
“…In [34], the clustering perspective is used in an algorithm that iterates between a matching step and the selection of mean features (similarly to k-means); this algorithm is sensitive to the initialization used, and multiple iterations are typically needed in order to achieve convergence.…”
Section: Clusteringmentioning
confidence: 99%
“…Given the results shown in Figure 6(b), we can see that our approach obtains the best performance when the dropout rate is in the range of [0.4, 0.5] and the performance decreases fast as the dropout rate increases from 0.6 to 0.8. The sampling number has several optimal values in our evaluation range, including [20,30], [50,60] or [80, 90].…”
Section: E Discussionmentioning
confidence: 99%
“…The second category of methods use the spatial similarity among objects using, e.g., distances between the objects in pairwise graph matching [6,29], angular relationships of objects in hypergraph matching [34,42], spatial relationships built by four or more objects in clique matching [35], and a combination of multiple spatial relationships [5]. The third category of methods recognize object correspondences by enforcing the circle-consistent constraints in multiple views [10], e.g., based on convex relaxation [3], spectral relaxation [32] and graph clustering [50].…”
Section: A Correspondence Identificationmentioning
confidence: 99%
“…Methods in the third category use a graph representation of the problem. In [17] and [3], the authors have elegantly observed the equivalence relation between cycle consistency and cluster structure of the association graph. This observation is used to find a suboptimal solution to the problem based on existing graph clustering algorithms.…”
Section: A Related Workmentioning
confidence: 99%